Bloody genius - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers novels., 2019)
"Virgil Flowers will have to watch his back--and his mouth--as he investigates a college culture war turned deadly in another one of Sandford's "madly entertaining Virgil Flowers mysteries" (New York Times Book Review)"--